STRATEGI MANAJEMEN RISIKO KREDIT UNTUK STABILITAS KEUANGAN DI SEKTOR PERBANKAN - Alfiana, Alfiana; Judijonto, Loso; Al-Amin, Al-Amin (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study aims to analyze effective credit risk management strategies in improving financial stability in the banking sector through the literature study method. Various relevant literatures were analyzed to identify key strategies in credit risk management. The main findings of this study indicate that the implementation of a strict and continuous credit supervision system, including periodic evaluation and the use of analytical technology for early risk detection, is essential. Credit portfolio diversification was identified as an effective method to reduce concentration risk and prevent large losses in one sector or region. In addition, data-driven credit assessment processes and advanced risk models are crucial to improving credit quality. The research also emphasized the importance of adequate reserves and provisions as a buffer against potential losses. In addition, human resource development through regular training was identified as an important aspect in strengthening risk management capabilities. The study also underscores the importance of compliance with international banking regulations such as Basel III in maintaining financial stability. Overall, the study concludes that implementing a comprehensive credit risk management strategy can significantly create a more resilient and stable banking system amidst global economic fluctuations